Pelatihan Menulis Efektif untuk Siswa Sekolah Menengah Atas di Kota Sorong - Taryono, Mohamad Rizal; Rahmatullah Bin Arsyad; Muh. Fathurrahman; Abu Bakar; Rinda Hardianti; Nhindi Sumai; Iriani Suci Kharmilah (Abdimas: Papua Journal of Community Service, 2025)
This community service activity aims to improve the language competence and skills of high school students in writing using proper and correct language, understanding grammar usage well, and understanding spelling usage in an orderly manner. The methods used are lectures with slides and problem-based learning, namely analyzing the language errors in a journal article and summarizing it with paraphrases that are in accordance with the rules of proper and correct Indonesian language. The results indicate that students were able to improve their language proficiency and skills in writing using proper and correct language, understanding the proper use of grammar, and understanding the proper use of spelling in scientific language.